Chronic Energy Deficiency In Pregnancy is An Influential Factor In The Occurrence Of Stunting In Toddlers - Nafisa, Triya Husna; Saptanto, Agus; Ratnaningrum, Kanti; Prihardini, Oky Rahma (Jurnal Ilmu Kedokteran, 2025)
Stunting refers to one of the health issues that often occurs in toddlers. A failure in growth brought on by chronic malnutrition and health issues during growth is known as stunting. Stunting can be caused by various factors. There have been many studies that discuss risk factors for stunting, but there are still differences in research results from various risk factors for stunting including maternal factors. The objective of this research is to analyze the influence of the maternal factors on the stunting’s prevalence in toddlers in the working site of Pakis Aji Health Center, Regency of Jepara. This is an analytic observational study using a case-control approach. The case group consists of stunted toddlers in the ages 24-59 months, while the control group consists of non-stunting toddlers between the age of 24 months and 59 months. The sampling method employed successive sampling. The research data included both primary and secondary data. Chi-square as well as logistic regression tests were used to analyze the topic. Result in this study show a significant effect of the history of Chronic Energy Deficiency (CED) in mother’s pregnancy (p-value = 0.009; OR = 3.619) and employed mothers (p-value = 0.026; OR = 3.143) with the occurance of stunting in children aged 24-59 months. While maternal age during pregnancy, mother’s education level, history of hypertension in mother’s pregnancy, and history of anemia in mother’s pregnancy had not affect the occurance of stunting in toddlers. The results of multivariate analysis showed that a history of CED during pregnancy was the most influential factor in the occurrence of stunting. In conclusion, CED during pregnancy is the most influential maternal’s factors in the occurrence of stunting in toddlers.